Preventive injunctions for violence between relatives in the light of the case law: with particular reference to the examination of the relationship between the parties in the fact-finding phase - Pál, Szilvia (Debreceni Jogi Műhely, 2025)
After a concise summary of the essence of the preventive restraining order in cases of violence between relatives, the paper presents the Hungarian case law on the application of this legal instrument – perhaps focusing on the most difficult issue to decide in these cases: which circumstances and based on which arguments the courts order preventive restraint, and in which circumstances and based on which arguments they choose to reject the application for a preventive restraint order or not to order preventive restraint. By examining the question of how the courts in proceedings for preventive restraining orders establish the facts and how they determine whether violence between relatives has occurred, the paper will then focus on a question not yet addressed in the legal literature, namely the exploration of the relationship between the parties, taking into account basic principles of family psychology. It will draw attention to a line of fact-finding and thinking that may help to answer the most difficult questions in these proceedings, especially in cases where the answer is not yet available: Whether or not violence between relatives has occurred and whether or not a preventive restraining order is necessary in a given case, where an allegation is set against a denial.